EFFECT OF WORK DISCIPLINE ON EMPLOYEE ACHIEVEMENT AT DINAS PERDAGANGAN PROVINSI SULAWESI SELATAN - Nur Awaliah Widarti; Mahlia Muis; Julius Jilbert (Paulus Journal of Accounting (PJA), 2023)
The final goal to be achieved from this study is to find out how work discipline influences employee achievement at the South Sulawesi Trade Office. This study uses 2 variabless, namelyy the independentt variable is work discipline (X) and the dependent variables is work performance (Y). The population of this research is all employees of ASN as many as 75 employees. Data was collected using documentation and questionnaire methods. Descriptive statistical analysis, prerequisite test, and multiplen linear regressionn analysis were used to test the hypotheses and processed with the help of IBM SPSS Statistics 21 were usedd to analyzee the data. The final results of this study indicate that work discipline affects the employee achievement of the South Sulawesi Provincial Trade Service Office.